The Impact Of RFID Technology In Retail Supply Chain Management - Najfabadi, Farnaz Soheili (2006)
The objective of this research is to identify perception of managers towards the advantages and obstacles of implementing RFID technology in retail supply chain and also identify the relationship between cost effectiveness of RFID and the size of the organization.